2010
DOI: 10.1002/hbm.20982
|View full text |Cite
|
Sign up to set email alerts
|

fMRI study of mesial temporal lobe epilepsy using amplitude of low‐frequency fluctuation analysis

Abstract: Various functional imaging tools have been used to detect epileptic activity in the neural network underlying mesial temporal lobe epilepsy (mTLE). In the present fMRI study, a data-driven approach was employed to map interictal epileptic activity in mTLE patients by measuring the amplitude of low-frequency fluctuation (ALFF) of the blood oxygen level-dependent (BOLD) signal. Twenty-four left mTLE patients and 26 right mTLE patients were investigated by comparing with 25 healthy subjects. In the patients, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
168
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(191 citation statements)
references
References 47 publications
20
168
1
2
Order By: Relevance
“…Both mesial temporal lobe and idiopathic generalized epilepsy have shown increased amplitude of low‐frequency BOLD signal fluctuations in thalami, temporal cortices, and default mode network (DMN) (Wang et al., 2014; Zhang et al., 2010). It is also shown that there might be relation between VLF differences on white matter and BOLD signal detection (Gawryluk, Mazerolle, & D'Arcy, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Both mesial temporal lobe and idiopathic generalized epilepsy have shown increased amplitude of low‐frequency BOLD signal fluctuations in thalami, temporal cortices, and default mode network (DMN) (Wang et al., 2014; Zhang et al., 2010). It is also shown that there might be relation between VLF differences on white matter and BOLD signal detection (Gawryluk, Mazerolle, & D'Arcy, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ALFF measures the amplitude of fl uctuation of individual voxels [6] . It has been used to differentiate two resting conditions [7] and differentiate patients with epilepsy from normal controls [8] . During the resting state, regions exhibiting higher ReHo [3] and ALFF [6,7] than other regions are in line with the location of the default mode network and have the highest metabolic rate as measured by positron emission tomography.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]6 Graph-theory analysis of resting-state fMRI data from patients with epilepsy also revealed decreased functional nodal topologic properties of the DMN that were positively correlated with disease duration. 8,[11][12][13][14] Regional homogeneity analysis of resting-state fMRI data was even used as a presurgical tool for seizure identification in patients with MR-negative focal epilepsy. 15 Thus, various models of data analysis have helped in understanding epilepsy further, and now there is increasing interest in using these models to reclassify epilepsy as a focal epileptogenic area 10,15 or as a network of seizure-generating areas.…”
mentioning
confidence: 99%